2022
DOI: 10.7759/cureus.30631
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Medicaid Expansion and Diabetic Ketoacidosis Hospitalizations

Abstract: Background and objectiveDiabetic ketoacidosis (DKA) is a potentially fatal complication of uncontrolled diabetes and remains a significant source of morbidity and mortality even though it is considered preventable. Diabetes is a chronic illness that requires constant monitoring and regular check-ups. Delaying or foregoing necessary diabetes care due to a lack of health insurance can result in severe complications. The Affordable Care Act (ACA) Medicaid expansion is intended to increase access to healthcare and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, hospital-acquired and ventilator-associated pneumonia cases that required intensive care have been found to have increased hospitalization time and costs 21,22 . The impact of development of DM and infectious complications in DM patients on hospitalization costs has also been frequently reported [23][24][25] . In other studies, oral bacterial infection and poor oral health were shown to be risk factors related to surgical site infection after various cancer and cardiovascular surgical procedures 9,[26][27][28][29] , while a relationship between oral microbial colonization and ventilator-associated pneumonia in patients in intensive care units has also been reported 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hospital-acquired and ventilator-associated pneumonia cases that required intensive care have been found to have increased hospitalization time and costs 21,22 . The impact of development of DM and infectious complications in DM patients on hospitalization costs has also been frequently reported [23][24][25] . In other studies, oral bacterial infection and poor oral health were shown to be risk factors related to surgical site infection after various cancer and cardiovascular surgical procedures 9,[26][27][28][29] , while a relationship between oral microbial colonization and ventilator-associated pneumonia in patients in intensive care units has also been reported 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, people from an area with the lowest income quartile had a 46% increase in the odds of four or more DKA readmissions in a given calendar year, while a patient with Medicare insurance had over a threefold increased odds of this outcome compared with those with private insurance [59]. In the USA, policy solutions such as increasing access to health insurance, affordable insulin, medical care, nutritious food and housing would be expected to reduce the incidence of DKA [157].…”
Section: Section 7 How Can Dka and Hhs Be Prevented?mentioning
confidence: 99%
“…In a recent study, people from an area with the lowest income quartile had a 46% increase in the odds of four or more DKA readmissions in a given calendar year, while a patient with Medicare insurance had over a threefold increased odds of this outcome compared with those with private insurance (59). In the U.S., policy solutions such as increasing access to health insurance, affordable insulin, medical care, nutritious food, and housing would be expected to reduce the incidence of DKA (157).…”
Section: Non-insulin Agents Discharge Plansmentioning
confidence: 99%